Analysis of the Influence of the Quality of Dental and Oral Health Service on the Level of Patient Satisfaction at RSI Malahayati Medan - Japardi, Angely; Theo, Deli; Amira, Asriwati (PROMOTOR, 2025)
Background: The quality of health services can affect the degree of hhealth and well- being of patients, because satisfied patients will come for treatment again. The purpose of this study is to analyze the effect of dental and oral health services on patient satisfaction at the Malahayati Islamic Hospital. Methodology: This research uses a quantitative analytic survey research with cross sectional study design. The location of this study was conducted at the Malahayati Islamic Hospital. The study population was all out patients who visited with Total Visit on May 2023-August 2023 of 422 patients. The number of samples in this study were 81 people. The technique used is purposive sampling. Survey data were analyzed using the chi-square test and logistic regression. Results: The results showed that there was an effect of tangibility, reliability, responsiveness, assurance and empathy for dental and oral health services on patient satisfaction. Conclusion: Based on the results of the study note that tangible, reliability, responsiveness, assurance and empathy affect patient satisfaction at the MalahayatiPublic Health Center in Medan and the variables that most influence on patient satisfaction are responsiveness variables. The suggestion for this research is that the Hospital should maintain customer satisfaction by increasing the quality of service and completing the infrastructure that is still lacking so that patient satisfaction is fulfilled and patients become loyal.